Liquid metal-filled magnetorheological elastomer with positive piezoconductivity - Guolin Yun (Nature Portfolio, 2019)
Liquid metal-filled elastic composites for strain sensing devices exhibit reduced conductivity under strain, which limits their usefulness. Here, the authors report a positive piezoconductive effect in liquid metal-filled magnetorheological elastomers and illustrate proof-of concept applications.